The relationship between professional competence and medical error tendency among final-year nursing students. - Zeyrek, Arife Şanlialp; Arslan, Sümeyye; Fidan, Özlem (Work, 2026)
Background: High-quality healthcare relies on competent and prepared nursing professionals. Final-year nursing students play a key role in preventing medical errors, thus ensuring patient safety. Objective: This study aimed to examine the professional competencies of final-year nursing students, medical error tendency, and the relationship between these variables. Methods: A descriptive-correlational design was used. Data were collected using the Personal Information Form, Medical Error Tendency Scale in Nursing, and Competency Inventory of Nursing Students. Higher competency scores indicate higher professional competence, while higher scores on the Medical Error Tendency Scale indicate a lower medical error tendency. Results: Students showed high professional competence (M = 6.22, SD = 0.63) and low medical error tendency (M = 4.52, SD = 0.39). The highest score on the Medical Error Tendency Scale sub-dimensions was in Medication and Transfusion Practices (M = 4.68, SD = 0.34), and the lowest in Patient Monitoring and Equipment Safety (M = 4.29, SD = 0.53). Students scored highest in ethics and accountability (M = 6.43, SD = 0.61) and lowest in clinical biomedical science (M = 5.83, SD = 0.93). A significant positive correlation was found between professional competence and medical error tendency (r =.713, p <.01). Since high scores indicate a lower medical error tendency, it was concluded that as nursing students' professional competence increases, their medical error tendency decreases. General clinical skills, critical thinking, and ethics significantly predicted medical error tendency. Conclusions: The study highlights the importance of professional competence in reducing medical error tendencies among nursing students. Enhancing competencies, particularly in clinical skills, critical thinking, and ethics, through competency-based and simulation-supported education can contribute to improved patient safety outcomes.